1999
DOI: 10.1109/23.785737
|View full text |Cite
|
Sign up to set email alerts
|

Silicon detectors with 3-D electrode arrays: fabrication and initial test results

Abstract: The first three-dimensional detectors with n and p electrodes that penetrate through the silicon substrate have been fabricated. Some expected properties, including low depletion voltages, wide voltage plateaus before leakage current limits are reached, and rapid charge collection are reviewed. Fabrication steps and initial test results for leakage currents and infrared signal detection are covered. The authors conclude with a description of current work, including fabrication of active-edge detectors, ones wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(94 citation statements)
references
References 27 publications
5
89
0
Order By: Relevance
“…Like in a standard 3D detector, the electrode columns were produced by first etching holes in the substrate, then filling them [3]. The etching was done with an Inductively-Coupled Plasma (ICP) etching process, using an aluminium/copper mask to protect the unetched areas.…”
Section: Simulation Of 3d Detectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like in a standard 3D detector, the electrode columns were produced by first etching holes in the substrate, then filling them [3]. The etching was done with an Inductively-Coupled Plasma (ICP) etching process, using an aluminium/copper mask to protect the unetched areas.…”
Section: Simulation Of 3d Detectorsmentioning
confidence: 99%
“…The first 3D detectors were produced nearly a decade ago [3], but research into these detectors has increased over the last few years, for a couple of reasons. Firstly, fabricating the electrode columns in these detectors requires the use of specialised micromachining techniques.…”
mentioning
confidence: 99%
“…The combination of semiconductor sensor processing with deep reactive ion etch (DRIE) methods, as used for manufacturing of micro electro-mechanical systems (MEMS), allows for the fabrication of Silicon Pixel sensors where the electrodes are implemented as vertically etched columns, fully or partially penetrating the Silicon bulk [1] [2]. The general principle applied to a wide-pixel geometry is illustrated in Figure 1.…”
Section: Radiation Hard 3d Pixel Sensorsmentioning
confidence: 99%
“…Almost edgeless devices can thus be implemented. This technology has been proposed by Parker and Kenney [13] in 1994, and it has undergone several years of intense development. Recent test beam data [14] have demonstrated that the technology proposed by Parker and Kenney can deliver the expected performance.…”
Section: Pos(vertex 2007)039mentioning
confidence: 99%